Emerging Premarital Sexual Behavior among Adolescent in Indonesia: The impact of Knowledge, Experience, and Media Use to Attitudes - Ira Nurmala1,2, Citra Ervina Ahiyanasari2 , Muthmainnah2 , Anggun Wulandari2 , Yuli Puspita Devi2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The number of premarital sexual behavior among adolescent is increasing around the globe. Research showedattitudes influence the increasing number of premarital sexual behavior among adolescent. However, thereis a gap in understanding factors influencing the positive attitudes of adolescent. Therefore, this study aimsto determine the three factors affecting attitudes (knowledge, experience, and access to media) to preventpremarital sex behavior among adolescent. This study was a quantitative research with cross-sectionaldesign in determining the sample. The simple random sampling method was used and data were collectedfrom 75 high school students of first, second, and third grade (15-19 years old). The knowledge, experience,and the use of media is helpful for adolescent but only to a certain extent. Their positive attitude formeddue to other factors that is beyond the scope of this research. This study showed that positive attitudes ofadolescent is necessary to help them preventing premarital sex behavior that leads to many health problems.Therefore, we need to revisit existing health programs for adolescent to reinforce their positive attitudes tohelp them making healthy life choices